Effectiveness of tidal control gates in flood-prone areas during high tide appearances - Yasmin, Mohd Nazri; Mohd Razali, Siti Fatin; Sharil, Suraya; Wan Mohtar, Wan Hanna Melini; Saadon, Khairul Adzim (Frontiers in Environmental Science, 2022)
Managing floods in low-lying coastal plains are challenging because of the complexity of the underlying physical processes and the combination of factors such as high tides and, severe storm events. In Malaysia, there were concerns from local people about the construction of a tidal control gate that is believed to contribute to the causes of local flooding. The performance of tidal control gates as flood control structures was studied to determine their significance and importance. The objective of this study is to evaluate the effectiveness of tidal control gates in reducing the impact of floods during high tide with severe storm events. The methodology of the study requires the usage of the hydrodynamic model using design rainfall for three scenarios with land use changes in 2015 and 2020. Three feasible scenarios were identified and further investigated. Scenario 1: without a tidal control gate; Scenario 2: with the existing tidal control gate fully open; and Scenario 3: with the existing tidal control gate fully closed. The simulation result clearly shows that the floodplain is smaller in 2015 as compared to the land use changes in 2020 because of land use permeability. In addition, the floodplain for Scenarios 2 and 3 in 2015 and 2020 is 2% to 3%, respectively, smaller than that of Scenario 1 for the 20-year ARI and 3% to 8%, respectively, smaller for the 100-year ARI. The results showed the influence of heavy rainfall whereby the maximum downstream discharge increment varied from 4.06% to 4.28% during high tide. Whereas the flow level for the 100-year ARI shows an increment from 0.52% to 1.53%. If the TCG is not operated properly it will cause the tidal water to flow back into the upstream areas thus exposing to an increased floodplain area ranging from 2.3% to 8.4%. which emphasizes the importance of operational methods for tidal control gate in determining its efficiency. However, further studies should also be done on the reduction of damage value involved with the construction of TCG, its value in saving lives, property and in other parts of the world having different tidal variations.